Factors Affecting Sustainability Reporting Disclosure - Febriyanti, Galuh Artika (E-Jurnal Akuntansi, 2021)
The aim is to determine the factors affecting sustainability reporting with a focus on firm age, woman presence, profitability, and leverage. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020. Total population consist of 103 firm-years that consistently publish sustainability reporting for the period 2018-2020. samples consist of 33 firm-years based on the criteria.Testing the data using multiple linear regression, the results showed that firm size, woman presence on board of commissioners’, and profitability do not have a significant effect on the sustainability reporting disclosure. However, woman presence on board of directors and leverage had a significant effect on the sustainability reporting disclosure. Keywords : Firm Size; Woman Presence On Board Of Commissioners; Woman Presence On Board Of Directors; Profitability; Leverage.